ABOUT THE CRITICAL APPROACH TO THE HISTORICAL SOURCE (Review on the article: Hakobyan H.E., Khapizov Sh.M. “A Journey to Armenia, Turkey and Cilicia” by the Bishop Vardan Odznetsi as an important source on the history of the Caucasus of the 18th – 19th centuries // History, archeology and ethnography of the Caucasus. Vol. 16. No. 1. 2020. P. 76-84) - Gadzieva, Ul'via S. (History, Archeology and Ethnography of the Caucasus, 2020)
This publication is a response to the article by H.E. Hakobyan and Sh.M. Khapizov “A Journey to Armenia, Turkey and Cilicia” by the Bishop Vardan Odznetsi as an important source on the history of the Caucasus of the 18th–19th centuries”. The information given in the article refers exclusively to ethno-political events in the South Caucasus at the end of the 18th century, which does not allow us to evaluate the work of Odznetsi as “an important source on the history of the Caucasus of the 18th–19th centuries.” The authors consider this source outside the historical geography of the region of the 18th century, when a number of khanates and sultanates existed in the eastern part of the South Caucasus, headed until the beginning of the 19th century Azerbaijani Turkic dynasties, and the territory of historical Armenia was the region of Ottoman Turkey in Anatolia. Some information of Odznetsi given in the article regarding historical events that took place in this region at the end of the 18th century not confirmed by other sources of the 18th–19th and modern historiography. This is especially true of information on the ethno-demographic situation in the region in the 18th century. It should be noted the uncritical approach of the authors to the source. The authors of the article could have avoided the noted errors if the information of Bishop Vardan Odznetsi (author of the second half of the 19th century) were correlated with more reliable sources and documents of the 18th–19th centuries. The erroneous statements made distort the ethno-political picture of the South Caucasus of the 18th century. This demonstrates the need for a critical approach when analyzing a written source, a historian’s responsible, impartial and objective view of the modern history of the Caucasus, the events of which are echoed on the recent history of the region.
Keywords: Azerbaijan; South Caucasus; Karabakh; Nakhchivan; Irevan (Erivan) Khanates.